Contemporary approaches to psychological assessment / [Edited by] Scott Wetzler; Martin M Katz - Katz, Martin M.
This volume (the first in the series) comprises 17 contributions in five main sections: strategies of psychological assessment, specific methodologies, cognition and intellect, ego functions, and related issues. Annotation copyright Book News, Inc. Portland, Or.